The Implementation of Picture Description to Encourage Writing Participation of Deaf Students in Special School (Scripta : English Department Journal, 2026)
This study aims to examine how picture description is implemented in writing instruction for deaf students and its impact on student participation during writing activities at a special education school. This study employs a qualitative descriptive approach, involving one English teacher and seven deaf 10th-grade students at a special education school in Medan. Research data were collected through classroom observations, semi-structured interviews, and documentation, and were then analysed using thematic analysis. The results indicate that picture description activities were implemented through the use of simple, easily understandable images, vocabulary introduction, the construction of simple sentences, and the provision of assistance and corrections by the teacher during the learning process. Furthermore, the findings indicate that the use of picture description enhances students’ engagement, motivation, self-confidence, and cognitive involvement in writing activities. This strategy also helps students produce writing at the sentence level and fosters a more active, engaging, and supportive learning environment for deaf students.